Voltammetric determination of taurine in energy drinks after o-phthalaldehyde-ethanethiol derivatization - Nawar, Amir Shaaban Farag Moham; Klikarová, Jitka; Česlová, Lenka; Vytřas, Karel; Sýs, Milan (Elsevier, 2019)
A completely new voltammetric method has been developed for quantitative determination of food additive Taurine (Tau) in energy drinks. This electroanalytical method is based on voltammetric oxidation of o-phthalaldehyde-ethanthiol derivative of Tau at glassy carbon electrode in 95% methanol containing 0.1 mol L−1 lithium perchlorate. Working conditions necessary for quantitative Tau derivatization reaction and electrochemical detection using square wave voltammetry were optimized. Linear range from 1.0×10−5 to 1.0×10−4 mol L−1 characterized by coefficient of determination 0.9998, limits of quantification 6.8×10−6 mol L−1 and detection 2.1×10−6 mol L−1 were obtained at pulse amplitude 50 mV and frequency 80 Hz. Analytical method of calibration curve was used for evaluation of Tau content in several commercially available energy drinks. The procedure was validated using standard reference high performance liquid chromatography (HPLC) method. Both methods showed nearly identical Tau content, around 0.35% (w/w). Besides its reliability to the Tau determination, that is totally comparable to reference method used, present voltammetric approach is more advantageous on the economic and simplicity basis. Finally, developed voltammetric method could find employment in food quality control.
Voltametrické stanovení taurinu v energetických nápojích po derivatizaci o-ftalaldehyd-ethanethiolem
Keywords: Glassy carbon electrode; food analysis; o-phthalaldehyde; derivatization; square wave voltammetry; taurine; Elektroda ze skelného uhlíku; analýza potravin; o-ftalaldehyd; derivatizace; voltametrie s obdélníkovou vlnou; taurin